Customer loyalty towards the usage of public transportation among non-residential students in Lembah Bujang / Nur Athirah Mohd Rosli and Nurul Aimie Kamarudzaman - Mohd Rosli, Nur Athirah; Kamarudzaman, Nurul Aimie (2017)
Public transportation refers to the transport that is provided to the public whereby it includes the services that using shared vehicles in providing mobility to the public. The study to examine the relationship between comfort, reliability, facility and safety with the customer loyalty towards the usage of public transportation among non-residential students of UiTM Kedah in Lembah Bujang. A sample 278 of non-residential students of UiTM Kedah were selected for this study. In this study, stratified random sampling technique were used. The result indicates there are positive correlations between comfort, reliability, facility and safety with the customer loyalty towards the usage of public transportation. The most significant factor that related with customer loyalty towards the usage of public transportation was reliability.